2020
DOI: 10.1371/journal.pone.0230437
|View full text |Cite
|
Sign up to set email alerts
|

Examination of multilevel domains of minority stress: Implications for drug use and mental and physical health among Latina women who have sex with women and men

Abstract: There has recently been growing attention and concern in the U.S. on the detrimental drug use and related health conditions impacting diverse sexual minority populations. While some evidence indicates that bisexual women are at increased risk of substance use, little attention has been given to disadvantaged and racial/ethnic minority bisexual women, who are particularly vulnerable to a complexity of stressors and risk. Using data from a 15-year longitudinal study in San Antonio, Texas, the current study exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…(1) Deep tissue infections are still a major problem currently. 85 Photodynamic inactivation can treat bacterial infections on the surface, and chemistry inactivation may introduce strong systemic toxicity. Fortunately, SDT, with no thermal effects, fewer side effects, effectiveness in deep tissue, and non-invasive treatment, has been widely used in antibacterial fields.…”
Section: Discussionmentioning
confidence: 99%
“…(1) Deep tissue infections are still a major problem currently. 85 Photodynamic inactivation can treat bacterial infections on the surface, and chemistry inactivation may introduce strong systemic toxicity. Fortunately, SDT, with no thermal effects, fewer side effects, effectiveness in deep tissue, and non-invasive treatment, has been widely used in antibacterial fields.…”
Section: Discussionmentioning
confidence: 99%
“…The San Antonio Latina Trajectory Outcomes (SALTO) study is a longitudinal community-based study examining the long-term health outcomes of drug use and intimate partner violence among a cohort of Mexican American women that were originally recruited and interviewed as adolescents between 1999 and 2001 [18,22,[61][62][63][64][65][66]. Eligibility criteria for Proyecto SALTO and the original study included being a Mexican American female, being aged 14-18 at the time of the original study, and being associated with one of 27 male street gangs from the catchment area [67,68].…”
Section: Methodsmentioning
confidence: 99%
“…The research has shown that this type of stress is cumulative, intersectional, specific to SGM’s stigmatized status, and related to other stressors such as violence, harassment, and sexual assault. Amid this progress lies a paucity of research on health disparities among SGM Latinas, particularly Latina women who have Sex with Women and Men (WSWM) ( Cepeda et al, 2020 ). Significantly less is known about Latina WSWM who are positioned at the intersection of multiple marginalized identities, which relegates them to a hidden social status as “marginal members within marginalized groups” ( Purdie-Vaughns & Eibach, 2008 , p. 5).…”
Section: Introductionmentioning
confidence: 99%
“…The sample of our exploratory study is derived from a 20-year longitudinal cohort of Mexican American women ( Cepeda & Valdez, 2010 ; Cepeda et al, 2020 ) who reported having had sex with both women and men. This cohort represents a subset of participants from the San Antonio Latina Trajectory Outcomes Study (Proyecto SALTO).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation